2018
DOI: 10.5465/ambpp.2018.14696abstract
|View full text |Cite
|
Sign up to set email alerts
|

The Nurturing of ‘Good’ Capitalists: Prisoners and Private Prison Labour

Abstract: This paper draws on a ten-month ethnographic study of private prison work in a UK prison to drawn attention to the prevalence of neoliberalism; even in an institution as secreted and isolated as a prison, the neoliberal ideology can flourish. Prisoners expressed attitudes heavily influenced by consumer culture and egoistic individualism. Most participants expressed a desire to become profitable entrepreneurs. On this basis, it should come as no surprise that prisoners admired the organizations sending work int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Butler (1999) views gender as provisional, shifting, contingent and performed, and is critical of heteronormativity within society. Drawing on this understanding, ethnographers can negotiate their gender and manage their image (Baum-Talmor, 2019;Lumsden, 2009;Poulton, 2012;Pandeli, 2015;Richards, 2018). Yet, it has been suggested that researchers can never be in complete control of the impressions they make (Baum-Talmor, 2019), and consequently some may experience anxieties around what to wear when entering the field and how their gender is expressed (Poulton, 2012).…”
Section: Gender and Image Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Butler (1999) views gender as provisional, shifting, contingent and performed, and is critical of heteronormativity within society. Drawing on this understanding, ethnographers can negotiate their gender and manage their image (Baum-Talmor, 2019;Lumsden, 2009;Poulton, 2012;Pandeli, 2015;Richards, 2018). Yet, it has been suggested that researchers can never be in complete control of the impressions they make (Baum-Talmor, 2019), and consequently some may experience anxieties around what to wear when entering the field and how their gender is expressed (Poulton, 2012).…”
Section: Gender and Image Managementmentioning
confidence: 99%
“…Other female ethnographers, from a variety of research settings, have also adopted this approach, selecting attire similar to their participant group to help them blend into the research environment. Such an approach is seen in work examining girl racers (Lumsden, 2009), prison inmates (Pandeli, 2015) and football fans (Richards, 2018).…”
Section: Gender and Image Managementmentioning
confidence: 99%
“…Although there are instances of successful examples of prison work that have proven to reduce recidivism (Marinetto and Pandeli, 2015; Shemkus, 2015), improvements to employability have been less evident (The Howard League for Penal Reform, 2011). In Pandeli’s (2015) ethnographic study of ‘orange-collar work’, such interventions (in this case private companies contracting prison labour) rarely provide appropriate skills for the outside world. This is by virtue of training and skills primarily in manual and unskilled assembly-based work that is generally concentrated within declining industries such as textiles and manufacturing or in the low-skilled and paid personal services industry – a sector well known for its precarious conditions (Atkinson and Rostad, 2003).…”
Section: Punitive Labour Geographiesmentioning
confidence: 99%
“…This is by virtue of training and skills primarily in manual and unskilled assembly-based work that is generally concentrated within declining industries such as textiles and manufacturing or in the low-skilled and paid personal services industry – a sector well known for its precarious conditions (Atkinson and Rostad, 2003). In fact Pandeli argues that the mundanity of this work ‘deters many’ inmates from the real world of work and can have the opposite effect of inmates ‘learning not to labour’ (Pandeli, 2015: 213–14). Therefore ‘whilst prison labour continues to be a key feature of the modern prison its marketed rehabilitative purpose still sits on the back-burner whilst occupation, profit and other motives take precedent’ (Pandeli, 2015: 19).…”
Section: Punitive Labour Geographiesmentioning
confidence: 99%
See 1 more Smart Citation